Probabilistic Weibull reliability of a shaft design subjected to bending and torsion stress - Piña Monarrez, Manuel Román (2024)
The circular shaft serves as the axis of rotation for the components. It is subjected to flexion and tearing, indicating that fatigue is the mode of failure. The range of stresses resulting from the mean and alternating loads determines the occurrence of fatigue failure. The deterministic fatigue analysis, calculated using the stress average obtained from SN curves, can only represent the mean life. This is because the stress range is not a single number, and therefore it cannot provide the reliability level for the stress. The study employs the Weibull distribution to estimate loads and parameters for a probabilistic shaft design under bending and torsion. The minimum strength is assessed using corresponding stress analysis to determine the reliability index for the designed shaft.